˜They need to put that pen to paperâ: Interview with Susan Ntete - van Heerden, Martina (WritingThreeSixty, 2020)
Dr Susan Ntete is a lecturer in the English Department at the University of the Western Cape. Recently, she published her first novel called Ain’t Over Till It’s Ova. WritingThreeSixty had an online interview with her to learn more about the novel.